Big data and poverty governance under Australia and Aotearoa/New Zealand's "social investment" policies. Issue 2 (23rd August 2020) - Staines, Zoe; Moore, Charlotte; Marston, Greg; Humpage, Louise
Abstract: Surveillance and governance of the poor have been key foci for the critical social policy literature for some time, although scholarship regarding the role of big data in social policy – and how this might differ from previous forms of surveillance – is continuing to emerge. This article contributes to this literature by exploring the use of big data under Australia and Aotearoa/New Zealand's social investment approaches. Both seek to replace social policy spending with "investment" expected to produce future fiscal returns; in the words of a former Aotearoa/New Zealand Prime Minister, they aim to do "more with less". We argue that big data often provides a poor evidence base for social investment and can, instead, be better understood as part of a panoptic toolkit for poverty governance, mediating continuous surveillance, examination and normalisation of the body politic by enabling the discursive (re)construction of people's identities and subjectivities. This construction serves to exacerbate social inequalities and undermine the rights of ordinary citizens.